The issues in implementation of innovative strategies in teaching and learning physics - Sukri, Siti Noorsuhada; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
To overcome the challenges of the twenty first century, especially in science and technology sector, students need to be provided with the 21st century skills to assure their competitiveness in the globalization era. Science subjects include physics allows individuals to gain knowledge in science and subsequently apply the knowledge in life as well as to nurture innovative attitudes. The government realized that the culture of innovation needs to be applied and practiced by teachers in the process of teaching and learning as a first step to ensuring the young generation is equipped with creative and innovative thinking to drive the country become a developed nation by the year 2020. Modern society now requires an active individual, responsible, problem solver and decision makers who are able to face the challenges and be involved effectively in society. On that basis, various strategies have been used by previous researchers to produce students with such skills. Therefore, literature review has been conducted to identify elements and definitions of innovation in the field of physics education from previous studies. This paper also discusses about issues arising during the implementation of innovative strategies in teaching and learning physics in schools. In addition, recommendation for strengthening the implementation of innovative strategies in the process of teaching and learning physics in the classroom are also discussed.